What Attracts Guest to Stay? Brand Identity, Religiosity, and Reference Group towards Decision to Choose Sharia Hotel - Winka Alfi Jayanti; Sri Setyo Iriani (al-Uqud : Journal of Islamic Economics, 2020)
Indonesia has one of largest Muslim population in the world. Therefore, currently it is not surprising that Sharia Branding is currently widely used by business entities ranging from banking to the hospitality business. This phenomenon is observed in the city of Surabaya in which Sharia hotels are mostly found such as the Namira Syariah Hotel. Nevertheless, the growth in the number of consumers who stay in Syariah hotels is not as much as conventional hotels. Therefore, the purpose of this research is to (1) to analyze the effect brand identity on the decision of consumers to stay at the Hotel Namira Syariah Surabaya, (2) to analyze the effect the consumer religiosity on consumers decision to stay at the Hotel Namira Syariah Surabaya, (3) to analyze the effect of the reference group to the decision to stay at the Hotel Namira Syariah Surabaya. This type of research uses a causal research approach. The population in this research is infinite but have ever stayed at the Hotel Namira Syariah Surabaya only but to all Muslim who at least 17 years old. The sample collection technique used is non-probability sampling with the number of samples is 210 respondents. The research instrument used a questionnaire, while data analysis used multiple linear regression analysis. From the results of the discussion and analysis of the data, it can be concluded that there is a positive influence of brand identity, religiosity and reference groups on the decision to stay at the sharia hotel.